Validation of the Brazilian version of the World Health Organization Disability Assessment Schedule in individuals with diabetes mellitus - Shamyr Sulyvan de Castro; Camila Ferreira Leite; Franciele Rodrigues Nacci; Karolyne Stéfanie Sousa Barbosa; Marilita Falângola Accioly (Universidade de São Paulo, 2019)
ABSTRACT To evaluate the functioning of individuals with diabetes mellitus (DM) using a biopsychosocial model, recommended by the World Health Organization and sustained in the theoretical-conceptual framework of the International Classification of Functioning, Disability and Health (ICF), this study proposed validating the Brazilian version of WHODAS 2.0 (World Health Organization Disability Assessment Schedule). The 36-item version of WHODAS 2.0 was applied to 100 participants with DM as validation procedures, using the measurement of Diabetes Quality of Life Measure (DQOL-Brazil) and a dynamometry. The psychometric properties analyzed were internal consistency (Cronbach Alpha coefficient) and convergent and divergent external validity (Spearman correlation coefficient). The internal consistency analysis was appropriate, except for the "having a good relationship with people" domain in the alpha Cronbach coefficient. External validity analysis confirmed the convergence hypothesis between the correlate domains of the different tools. The exception was the "life activities" domain (WHODAS) with the left-hand dynamometry. The Brazilian version of the WHODAS 2.0 instrument is a valid instrument to assess the functioning of these individuals.